ROLE OF EMOTIONAL INTELLIGENCE IN VERBAL BEHAVIOUR PATTERNS IN THE CLASSES OF PRIMARY SCHOOL TEACHERS: A COMPARATIVE STUDY - TIWARI, GAURANG; PANDEY, ASHA (THE PRIMARY TEACHER, 2013)
The purpose of the study was to see role of Emotional Intelligence (EI) in verbal behaviour pattern of primary school teachers. Verbal behaviour pattern was measured by FIACs (Flanders Interaction Analysis Category System). Teachers were categorised in four groups– EHE (Extremely High EI), HE (High EI), ME (Moderate EI) and LE (Low EI) groups as per their level of EI. Various interaction ratios were computed as indices of verbal behaviour pattern. It was observed that teachers high on EI asked diversifi ed questions in classroom teaching and ensure active participation of students as compared to teachers low on EI.